PP.32.20: MAGNETIC RESONANCE IMAGING OF THE BRAIN IN PATIENTS WITH ACROMEGALY AND ARTERIAL HYPERTENSION. (June 2015) - Belichenko, O.; Vorontsov, V.; Averkieva, E.; Vladimirova, V.; Babaeva, A.
Abstract : Objective: To evaluate MRI diagnostic possibilities in patients with acromegaly and arterial hypertension (AH). Design and method: MRI was performed in group of 78 patients (46 male, 32 female aged from 39 to 58 y.o) with recently diagnosed acromegaly, and AH, and in control group of 25 hyperintensive patients without acromegaly and other endocrine disorders. All patients recieved hypotensive treatment. MRI included flair-, T1-, T2-weighted images. We evaluated the presence of ischemic gliosis, leucoareosis, perivascular changes in white matter, hyppocampus, basal nuclea, and hydrocephaly. Results: We divided all patients by two groups: with hypertension history less than 10 and more than 10 years. Patients with acromegaly and AH showed more brain changes than in control group. We also found more severe gliosis and leucoareosis in group with longer hypertension history. Perivascular changes were found in 90% patients, ischemic cysts (<10 mm), gliosis, leucoareosis - in 55%. In 25% focal changes (> 10 mm), associated with acute ischemic episodes, were found. Internal hydrocephaly were found in 50%. However, external hydrocephaly was found in 34% of patients, that is less than in control group (45%). We found correlation between appearance of ischemic changes and duration of AH. Dynamic examination after 3 years after surgery in 51 pts showed no considerable improvement of brain condition; in 10% we found mild deterioration of ischemic changes. Conclusions: MRI is a effective method of evaluation of brain changes and dynamic examination of patients with acromegaly and AH. Patients with acromegaly and AH have more severe brain ischemic changes than hypertensive patients without endocrine disorders.